Pengelolaan mandiri penyakit kronik degeneratif di Posyandu Lansia, Desa Wonorejo, Maron, Probolinggo - Nur Hamim; Yulia Rahmawati (Jurnal Dedikasi Masyarakat, 2021)
Degenerative chronic diseases, especially diabetes mellitus and hypertension, are a major concern in Indonesia, especially in East Java Province. In Probolinggo Regency, especially in Wonorejo Village, Maron, the number of cases of chronic degenerative diseases among the elderly is very high. To overcome this problem, community service activities were carried out by implementing research in the field gerontiki nursing and Posyandu management. Activity methods include lectures, healthy food demonstrations, blood pressure measurements, and simulations on managing Posyandu for the elderly. The results include increasing the knowledge and skills of Posyandu cadres regarding chronic degenerative diseases creating new cadres. Success factors include socialization, personal approach, and student involvement. Even though there are differences in participants' assumptions, initiatives to strengthen old cadres and create new cadres are important. Even though the simulation took a long time, the participants remained enthusiastic. This activity succeeded in increasing the role of elderly Posyandu cadres in managing chronic degenerative diseases, providing a positive impact on the health of the elderly in Wonorejo Village, Maron, and perhaps also the surrounding area.